DEVELOPING STUDENTSâ WRITING ABILITY OF STAIN KEDIRI THROUGH SCAFFOLDING STRATEGY IN THE PROCESS OF WRITING - Ningrum, Ary Setya Budhi (Lingua Scientia, 2013)
Abstract:The aim of this study was to develop the studentsâ writing ability by using scaffolding strategy in the process of writing at State College for Islamic Studies (STAIN) Kediri. This study employed a Classroom Action Research (CAR) as its methodology. All of students that belong to class A writing 2 academic year 2010/2011 were taken as the subjects of this study. There were three criteria of success offered to be achieved in this study. The implementation of scaffolding strategy in the process of writing showed that the studentsâ writing ability improved significantly and the students were enthusiastic and motivated in the teaching and learning process.Â Keywords: scaffolding strategy, writing process, Classroom action research